2013
DOI: 10.1007/s00253-013-5227-9
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL and microRNAs in the treatment of prostate cancer: therapeutic potential and role of nanotechnology

Abstract: Disruption of spatiotemporal behavior of intracellular signaling cascades including tumor necrosis factor alpha-related apoptosis-inducing ligand (TRAIL)-mediated signaling in prostate cancer has gained tremendous attention in the past few years. There is an increasing effort in translating the emerging information about TRAIL-mediated signaling obtained through experimental and preclinical data to clinic. Fascinatingly, novel targeting approaches are being developed to enhance the tissue- or subcellular-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Thus, Farooqi et al [3] suggested that miRNA regulation of TRAIL-mediated signaling in prostate cancer cells can provide potential biomarkers for the characterization of patients as responders and non-responders for TRAIL-based therapy. Recently, miR-135a was also reported to inhibit the proliferation of renal carcinoma [19], induce apoptosis in gastric cancer cells [48] and promote drug sensitivity in cancer cells[49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Farooqi et al [3] suggested that miRNA regulation of TRAIL-mediated signaling in prostate cancer cells can provide potential biomarkers for the characterization of patients as responders and non-responders for TRAIL-based therapy. Recently, miR-135a was also reported to inhibit the proliferation of renal carcinoma [19], induce apoptosis in gastric cancer cells [48] and promote drug sensitivity in cancer cells[49].…”
Section: Discussionmentioning
confidence: 99%
“…Though anti-cancer drugs such as Eulexin, Flutamide and Nilandron have been used for treatment of prostate cancer, their side effects have still occurred. Recent studies reported that TRAIL and microRNA (miR)s were suggested as potential biomarker or therapeutic potential in prostate cancer cells [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a multifaceted and genomically complex disease and rapidly emerging experimental evidence has started to shed light on wide ranging factors which underlie cancer development and progression. Confluence of information suggested various nanotechnological approaches to enhance delivery of anticancer agents to the tumor site [14][15][16][17] . Still, because of the degradation ability of PLGA, these materials can be drug carriers, which will, in turn, be released in these specific locations, thus decreasing the side effects caused by medicines to normal cells [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“… Nanoscale devices which are smaller than 50 nanometers can without issues enter most cells, while those smaller than 20 nanometers can circulate out of blood vessels as they circulate via the frame.  Nanoscale gadgets have the capability to substantially alternate cancer remedy for the higher and to dramatically growth the quantity of exceedingly effective therapeutic agents [86][87][88] .  Nanoscale constructs, for instance, have to characteristic customizable, targeted drug delivery cars capable of ferrying big doses of chemotherapeutic stores or healing genes into malignant cells even as sparing healthful cells, which may greatly, lessen or get rid of the frequently unpalatable facet effects that accompany many contemporary most cancers healing tactics [89,90] .…”
Section: Cancer Nanotechnologymentioning
confidence: 99%